(untitled) (Journal of Engineering, 2021)
This research analyzes the level of the short circuit effect of the Iraqi super network and decides the suitable location for the High Voltage Direct Current (HVDC) connections in order to obtain the best short circuit reduction of the total currents of the buses in the network. The proposed method depends on choosing the transmission lines for Alternating current (AC) system that suffers from high Short Circuit Levels (SCLs) in order to reduce its impact on the transmission system and on the lines adjacent to it and this after replacing the alternating current (AC) line by direct current (DC) line. In this paper, Power System Simulator for Engineering (PSS/E) is used to model two types of HVDC lines in an effective region of Iraqi networks and to perform comparative studies to test the location of Short Circuit Levels (SCLs) between an actual AC and AC/DC case study in a portion of the Iraqi national network. The results proved the effectiveness of this method in eliminating severe faults and unwanted short currents, and the results showed that the bipolar type is better in reducing Short Circuit Levels of the Iraqi network.